2015
DOI: 10.1002/biot.201400649
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulatory elements: Recent advances in understanding their mode of action and use for recombinant protein production in mammalian cells

Abstract: Successful generation of high producing cell lines requires the generation of cell clones expressing the recombinant protein at high levels and the characterization of the clones' ability to maintain stable expression levels. The use of cis-acting epigenetic regulatory elements that improve this otherwise long and uncertain process has revolutionized recombinant protein production. Here we review and discuss new insights into the molecular mode of action of the matrix attachment regions (MARs) and ubiquitously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…The source of MARs, the inserted position of MARs, and the type of host cells may affect transgene expression by MAR [5,30,37,38]. Moreover, gene copy numbers are related to transgene expression [39], and the methylation of DNA may reduce transgene expression [40][41][42]. Some reports have demonstrated that MARs improve the expression of transgenes through the recombination pathway of synthesis-dependent microhomology-mediated endjoining (MMEJ) [8,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The source of MARs, the inserted position of MARs, and the type of host cells may affect transgene expression by MAR [5,30,37,38]. Moreover, gene copy numbers are related to transgene expression [39], and the methylation of DNA may reduce transgene expression [40][41][42]. Some reports have demonstrated that MARs improve the expression of transgenes through the recombination pathway of synthesis-dependent microhomology-mediated endjoining (MMEJ) [8,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…opening element (UCOE), or other insulator elements in the expression vector [24 ]. Strong constitutive promoters such as the mouse cytomegalovirus major immediate early promoter/enhancer (mCMV-MIE), the human elongation factor-1 alpha promoter (hEF-1a), and the SV40 early promoter/enhancer (SV40E) are recommended as alternatives to the hCMV-MIE [25,26].…”
Section: Expression Vector Elementsmentioning
confidence: 99%
“…In the following section, each element will be briefly discussed (see also Table ). For further details the reader is referred to the review …”
Section: Strategies To Improve Transgene Transcription: Chromatin‐modmentioning
confidence: 99%